Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/1440-1681.13062
|View full text |Cite
|
Sign up to set email alerts
|

Azithromycin inhibits muscarinic 2 receptor‐activated and voltage‐activated Ca2+ permeant ion channels and Ca2+ sensitization, relaxing airway smooth muscle contraction

Abstract: Azithromycin (AZM) has been used for the treatment of asthma and chronic obstructive pulmonary disease (COPD); however, the effects and underlying mechanisms of AZM remain largely unknown. The effects of AZM on airway smooth muscles (ASMs) and the underlying mechanisms were studied using isometric muscle force measurements, the examination of lung slices, imaging, and patch-clamp techniques. AZM completely inhibited acetylcholine (ACH)-induced precontraction of ASMs in animals (mice, guinea pigs, and rabbits) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…This study was performed to investigate whether modulation of ASM biology by macrolides contribute to their clinical efficacy. Indeed, azithromycin induces autophagy in human bronchial ASM 15 and relaxes pre-contracted human bronchial muscle strips 17 . In vivo, macrolide administration decreases ASM mass in rodents with an induced asthma-like disease 18 21 and in healthy mice 51 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was performed to investigate whether modulation of ASM biology by macrolides contribute to their clinical efficacy. Indeed, azithromycin induces autophagy in human bronchial ASM 15 and relaxes pre-contracted human bronchial muscle strips 17 . In vivo, macrolide administration decreases ASM mass in rodents with an induced asthma-like disease 18 21 and in healthy mice 51 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanisms underlying these positive outcomes are unclear as the spectrum of action of macrolides goes beyond antimicrobial and immunomodulatory effects 11 . The modulation of airway smooth muscle (ASM) biology in vitro 14 17 and the decrease of ASM mass in experimental models of asthma by macrolides 18 21 might explain their attenuation of bronchial hyperresponsiveness 22 , 23 . However, these results need confirmation in humans as treatment success obtained in rodent models frequently fails to translate to clinical therapy 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Muscle force of TRs was measured as we previously reported elsewhere (Wang et al, 2019). Briefly, mice were sacrificed following intraperitoneal injection of pentobarbital sodium (150 mg/kg).…”
Section: Methodsmentioning
confidence: 99%
“…To detect airway hyperresponsiveness, mTRs were were obtained from the control, asthma, vandetanib and dexamethasone groups (Figures 2A-D). ACh, which is a receptor agonist (Wang et al, 2019) was applied to induce airway contraction. The results showed that the 100 μM ACh-evoked contraction of mTRs in the asthma group (Figure 2B), was much higher than that in the control (Figure 2A), dexamethasone (Figure 2C) and To further investigate the relaxant feature of vandetanib in vivo, we detected Rrs using forced oscillation technique (Figure 2F).…”
Section: Vandetanib Relieved Pathological Changes and Airway Hyperres...mentioning
confidence: 99%
“…Therefore, we sought to identify ion channels other than VDLCC involved in vandetanib-induced relaxation. NSCCs and VDLCCs were involved in ACh-induced smooth muscle contraction (Wang et al, 2019). Given that, ACh was employed to precontract mTRs.…”
Section: Vandetanib Relaxed Ach-induced Contraction In a Concentratio...mentioning
confidence: 99%